The Comparative Effectiveness of Prednisolone and Dexamethasone for Children With Croup: A Community-Based Randomized Trial. (November 2013) - Garbutt, Jane M.; Conlon, Bridget; Sterkel, Randall; Baty, Jack; Schechtman, Kenneth B.; Mandrell, Kathy; Leege, Erin; Gentry, Shannon; Stunk, Robert C.
Background . Although common practice, evidence to support treatment of croup with prednisolone is scant. Methods . We conducted a community-based randomized trial to compare the effectiveness of prednisolone (2 mg/kg/d for 3 days, n = 41) versus 1 dose of dexamethasone (0.6 mg/kg) and 2 doses of placebo (n = 46). Participants were children 1 to 8 years old with croup symptoms ≤48 hours, categorized as mild (42%) or moderate (58%). Results . There were no differences for those treated with dexamethasone or prednisolone for additional health care for croup (2% vs 7%, P = .34), duration of croup symptoms (2.8 vs 2.2 days, P = .63), nonbarky cough (6.1 vs 5.9 days, P = .81), nights with disturbed sleep for the parent (0.68 vs 1.21 nights, P = .55), and days with stress (1.39 vs 1.56 days, P = .51). Conclusion . There were no detected differences in outcomes between the 2 croup treatments for either child or parent.